STRATEGI PENINGKATAN NILAI PERUSAHAAN: Peran Struktur Modal, Pertumbuhan, dan Kepemilikan Institusional - Cahyani, Yenni; Sinaga, Nia Novita (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine the influence of Capital Structure, Company Growth, Institutional Ownership Structure on Company Value. The population used in this research was 86 property and real estate services sub-sector companies listed on the Indonesian stock exchange with a sample of 15 companies and 5 years of observation with a total sample of 75 data. This research was conducted using quantitative descriptive analysis. The object of this research is the Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Data collection was carried out using the purposive sampling method. The data analysis techniques used are classical assumption testing, panel data regression analysis and hypothesis testing. The results of this research conclude that simultaneously, capital structure, company growth and institutional ownership structure have a positive effect on company value in property and real estate services sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period, whereas partially capital structure does not influence on company value in property and real estate services sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period, company growth has a positive effect on company value for property and real estate services sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period , and it was concluded that the institutional ownership structure had no effect on company value in Property and real estate services sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The results of this research suggest that the company should increase the effective use of assets so that the company's share price can increase and be able to generate the expected profits. By increasing profits, the value of the company will also increase. This can attract the attention of investors to invest.